The effect of real estate purchase subsidies on property prices - Carla Krolage (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
This paper assesses to which degree housing purchase subsidies are capitalized into property prices. Using a large-scale micro data set on German house prices, I exploit the introduction of a new subsidy scheme in the state of Bavaria. My difference-indifference estimations at the Bavarian interstate border indicate that the prices of single-family homes increased by about 3.4% more in Bavarian border regions. This is consistent with a full capitalization of the subsidy. No effect is found for apartments, whose purchasers seldom qualify for the subsidy. A heterogeneity analysis confirms that the price effect is larger in segments of the real estate market with a higher exposure to the subsidy scheme. I also provide suggestive evidence that the subsidy scheme slightly stimulated construction activity. Overall, my results indicate that instead of making house purchases more affordable for families, the subsidy scheme led to a rise in house prices and mainly benefited sellers of properties.
Keywords: H22; H24; H71; R31; R38; 330; real estate market; housing subsidies; property prices